(untitled) (Journal of Guidance and Counselling Studies, 2024)
This study used a correlational research design to establish how emotional intelligence predict undergraduate students’ social adjustment. Two research questions and two null hypotheses guided the study. The sample for the study consisted of 582 year 1 regular undergraduate students drawn from the population of the study using a multi-stage random sampling procedure. Two instruments, the Emotional Intelligence Inventory (EII), the Barratt Impulsiveness Scale (BIS-R-21), and the Social Adjustment Questionnaire (SAQ), were used for data collection. Data collected were analyzed using Pearson Product Moment Correlation and regression analysis. The findings of the study revealed that, there is a low positive relationship between emotional intelligence and social adjustment among 100-level undergraduate students in public universities in Anambra State. Based on the findings of the study, it was recommended, among others, that the government should prioritize creating a more conducive learning environment for student’s social adjustment.